Open culture: shared knowledge - Méndez, Eva (Anuario ThinkEPI, 2015)
The current openness trend includes concepts such as transparency, democracy, sharing, collective, free, common, or commons, and working areas such as open access, open data, open linked data, dataset curation, open content, open research, open education, open innovation, or open knowledge. All these issues were addressed in the 13th Jornadas españolas de documentación (Fesabid 2015, 28-29 May, Gijón, Spain). The conference offered 3 tracks: 1) Public information, open data and collections: transparent administration and shared culture; 2) Open research: from open access to open data; and 3) Open education and new skills: reactivating the educational role of libraries and information services.
Keywords: Openness; Transparency; Open access; Open data; Open linked data; Dataset curation; Open research; Open education; Open innovation; Open knowledge; Fesabid 2015.